2006
DOI: 10.1007/s00247-006-0263-6
|View full text |Cite
|
Sign up to set email alerts
|

Can a fixed measure serve as a pertinent diagnostic criterion for large vestibular aqueduct in children?

Abstract: A CT scan threshold value, fixed and independent of age and sex, is thus legitimate for the diagnosis of vestibular aqueduct dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…There was no correlation between the size of the VA operculum or midpoint with age. This is in accordance with the study of Legeais et al [15] who found that there was no statistically significant variability in VA diameter as a function of age. The onset of SNHL as a presentation of EVA may be early after birth to adulthood with the highest frequency in childhood [16][17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 93%
“…There was no correlation between the size of the VA operculum or midpoint with age. This is in accordance with the study of Legeais et al [15] who found that there was no statistically significant variability in VA diameter as a function of age. The onset of SNHL as a presentation of EVA may be early after birth to adulthood with the highest frequency in childhood [16][17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 93%
“…7,[9][10][11][12][13][14] The value for the maximum normal VA midpoint width varies among authors. The published values include 1.4, 13 1.5, 4,11,12,14,15 1.9, 7 and 2.0 mm. 9,10 One publication did not refer to the midpoint width; instead, it defined a large VA as one with a "visible large aperture (Ն4 mm) and a small distance between the vestibule and traceable part of the VA nearest to the vestibule (Ն1 mm)."…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that there is no age-related variability in the dimensions of the VA has been confirmed in a study reporting the same findings in a group of 200 children. 15 A potential criticism of this work is the moderately high degree of correlation between the left and right ear measurements. Although our current report focuses on the percentile cutoffs based on 146 ears, we do illustrate the percentile cutoffs with respect to the left and the right ear separately in Table 1.…”
Section: Figmentioning
confidence: 93%
See 1 more Smart Citation
“…Thanks to these advantages, MDCT has permitted the recognition and characterization of inner ear anomalies not previously identified 2 , resulting in an optimal technique for the investigation of middle and inner ear pathologies and evaluation of anatomical variations in preoperative assessment 3 . Many diseases, such as malformations of the cochlea, otosclerosis or ossification of the cochlea, can be diagnosed unequivocally 4,5 .…”
mentioning
confidence: 99%